Effects of statistical pore characteristics on mechanical performance of selective laser melted parts: X-ray computed tomography and micromechanical modeling - Wang, Xue; Zhao, Liping; Fuh, Jerry Ying Hsi; Lee, Heow Pueh (Materials Science and Engineering: A, 2022)
Laser powder bed fusion (LPBF), one of the most powerful additive manufacturing techniques, has attracted broad interests from medical, aerospace and automotive industries. It is a powder bed fusion method, processing metallic and non-metallic materials in a layer-by-layer manner. However, such a layer based manufacturing process introduces internal defects such as pores into the final product, giving rise to negative effects on the mechanical performance. This paper is aimed towards providing a methodology for analyzing the effects of statistical pore characteristics on the mechanical behavior of the LPBF processed parts. Specifically, quantitative relationship among pore characteristics, such as statistical correlation between size and morphology/orientation of the pores, is established via X-ray computed tomography (XCT) for tensile specimens fabricated using a variety of energy input. The relationship among the pore features is compared before and after the tensile testing to gain deep insights on how the pore details affect the tensile behavior of the parts. Based on the quantitative correlation among the pore features, a micromechanical model is proposed to predict the mechanical properties of the materials, providing an alternative to the destructive tests for future LPBF users. The predicted results are benchmarked with classical analytical solutions, experimental data as well as reported numerical predictions.